Quality Control of Education in the Universities of Ukraine - RYBALKO, Yuliya; EPELBOIM, Olena (Journal of Education, Technology and Computer Science, 2014)
There are main criteria and components of education quality, the system of control of the quality of providing educational services on different levels: student – teacher – university represented in the article. The main provisions of carrying out quality assurance due to the nowadays dimensions by higher educational institutions are revealed.